2012
DOI: 10.1002/jcp.24241
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid regulates gap junction intercellular communication in human endometrial stromal cells through modulation of the phosphorylation status of connexin 43

Abstract: Previous studies revealed that gap junction intercellular communication (GJIC) among uterine stromal cells plays critical roles in modulating decidualization, neovasularization, and embryo implantation. Connexin (Cx) proteins are the major component of gap junctions and Cx43 is the most widely expressed connexin in endometrium. Phosphorylation of Cx43 was found to impair gap junction communication in this tissue. Using primary human endometrial stromal cells (ESCs) and a stable high telomerase-expressing ESC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 58 publications
5
54
0
Order By: Relevance
“…All three methods utilized in this study to functionally inhibit GJ function: high-and low-density cell culture, oleamide treatment, and siRNA transfection-mediated inhibition of Cx32 expression demonstrated that inhibiting the function of GJs led to a decrease in the hepatotoxicity of TNF-α. As a corollary, we also attempted to utilize retinoic acid (Wu et al, 2013) to enhance GJ function; however, after retinoic acid treatment, mass cell mortality occurred for unknown reasons. Therefore, the question of whether enhancement of the function of GJs can enhance the cytotoxicity of TNF-α to BRL-3A cells remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…All three methods utilized in this study to functionally inhibit GJ function: high-and low-density cell culture, oleamide treatment, and siRNA transfection-mediated inhibition of Cx32 expression demonstrated that inhibiting the function of GJs led to a decrease in the hepatotoxicity of TNF-α. As a corollary, we also attempted to utilize retinoic acid (Wu et al, 2013) to enhance GJ function; however, after retinoic acid treatment, mass cell mortality occurred for unknown reasons. Therefore, the question of whether enhancement of the function of GJs can enhance the cytotoxicity of TNF-α to BRL-3A cells remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether GJIC was required for the increase of adriamycin-induced cytotoxicity in cells with GJIC, the breast cancer cells Hs578T and MCF-7 were treated with chemical modulators of GJs prior and during exposure to 6 µM adriamycin [inhibitor, oleamide (22,23) or 18-α-GA (24,25); potentiator, RA (21,26)] at high density (GJ formed) or low density (no GJ formed). Fig.…”
Section: Influence Of Gj Potentiator On the Cytotoxicity Of Adriamycinmentioning
confidence: 99%
“…This disease is characterized by the ectopic localization of endometrial-like tissues in the pelvic cavity, and its pathogenesis involves uncontrollable cell proliferation and is associated with local invasion and distant metastasis. Among the numerous aspects of endometrial behavior regulated by RA are matrix metalloproteinase secretion, gap junctional intracellular communication and the production of various cytokines involved in stromal cell growth, adhesion and differentiation (Wu et al 2013). Interleukin 6 (IL-6), monocyte chemotactic protein 1 (MCP-1), tumor necrosis factor α (TNF-α), vascular endothelial growth factor (VEGF) and connexin43 are all aberrantly expressed in endometriotic lesions (Sawatsri et al 2000, SharpeTimms 2001, Nozaki et al 2006, Sidell et al 2010, Wu et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of these same genes can be modulated by ovarian steroid hormones (i.e., estradiol and progesterone) treatment (Vermot et al 2000, Li & Ong 2003, Rühl et al 2006, Fritzsche et al 2007). The retinoid pathway is known to play vital roles in endometrial development and differentiation (Tanmahasamut & Sidell 2005, Wu et al 2013, Nakajima et al 2016, as well as endometrial neovascularization (Sidell et al 2010) and blastocyst implantation (Han et al 2010, Ma et al 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation